Pralatrexate for refractory mycosis fungoides in two Japanese patients. Issue 5 (16th January 2021) - Teraishi, Mika; Oguro, Tokuko; Kusume, Ema; Kobashi, Haruka; Sano, Hozumi; Fujioka, Ai; Yamamoto, Mayuko; Nakajima, Hideki; Sano, Shigetoshi
Abstract: Pralatrexate has been approved for the treatment of relapsed/refractory peripheral T cell lymphomas. Studies in the U.S. also support the clinical efficacy of pralatrexate to treat advanced‐stage cutaneous T‐cell lymphomas, but outcomes in Japanese patients have not yet been reported. We herein describe two Japanese patients with heavily‐pretreated relapsed/refractory mycosis fungoides that were successfully controlled by pralatrexate.